EVALUASI PENERAPAN TEKNOLOGI PADA PROGRAM SEKOLAH LAPANGAN PENGELOLAAN TANAMAN TERPADU (SLPTT) PADI DI KECAMATAN BENUA KAYONG KABUPATEN KETAPANG - Adi Suyatno, Hesti Looviani A. Hamid A. Yusra (Jurnal Social Economic of Agriculture, 2014)
The agricultural sector in particular sub sectors of paddy crops is highly strategic sector and potential as the leading sectors in economic development. To realize the national rice surplus of 10 million tons in 2014, one of the strategies pursued by the government in increasing national rice production is driving the increase in rice productivity through Integrated Crop Management Field School (FFS-ICM), by applying 2 (two) component technology is the basic technology component and component technology of choice. In 2012 the District has implemented a program Benua Kayong FFS-ICM Rice with acreage of 600 hectares,consisting of 24 hectares of land Field Laboratory (FL) and 576 hectares of land non FL. The experiment was conducted in the Kecamata Benua Kayong, which is one of the regions implementing FFS-ICM Rice program in 2012. The problem is formulated in this study is how the application of technology in the program FFS-ICM Rice . The purpose of the study to determine the application of the technology in the program FFS-ICM Rice. The data collection was conducted in July to August 2013, using survey methods and interviews involving 85 farmer respondents with tools such as questionnaires. In the overall study population are members of farmer groups implementing FFS-ICM in Benua Kayong numbered 576 people. The results showed that the application of basic ICM technology components : a) All farmers have to use new varieties (100%), b ) Farmers use of quality seeds and labeled (71,76%), c ) Provision of organic material made ​​by burning straw in paddy fields (61,18%, d ) Population of 160,000 plants clumps / ha (54,12%), e ) Farmers do not do chemical fertilizers (62,35%), f ) farmers use pesticides to control the pest (100%). The application of technology components ICM options : a) The cropping pattern is rice - pulses are used (45,88%), b ) Removal of seeds is done at the age of 21 days after planting (48,24%), c ) The number of seeds planted was 1-3 stems per clump (100%), d ) cropping system used is cropping systems tiles (54,12%), e ) Watering is done by creating a channel or ditch (92,94%), f ) Weeding is done manually (94,12%), g ) Harvesting is done on time, but too late to do the threshing (47,06%). Application of ICM technology components by farmers included in categories according (61,54%) to the average score of 2, meaning that ICM technology components can already be applied to farmers in Benua Kayong although not yet. Therefore, the resulting productivity (42,13 Kw/Ha) has not reached the expected target (54,77 Kw/Ha). Keywords : Integrated Crop Management, Application of technology,maklumat, pesan, laporan, siaran warta berita, harian regional Rice